Analyzing Digital Marketing Strategies to Increase Student Enrollment in Private Universities: An Educational Management Perspective - Sarumaha, Martiman S (LP. Ma'arif Janggan Magetan, 2026)
This study aims to analyze digital marketing strategies in an effort to increase the number of new students in private universities from the perspective of educational management. This study also explores how educational management designs, implements, and evaluates digital marketing strategies in the context of increasingly dynamic competition in the higher education sector. This study uses a literature study method with a descriptive qualitative approach. Based on its analysis, this study concludes that effective digital marketing for private university enrollment hinges not on technical platform sophistication, but on its strategic integration within the institution's educational management framework. It identifies a critical